Konseling Pra-Nikah dengan Pendekatan Islami Bagi Remaja Menggunakan Al-Qur’an Dalam Meminimalisir Perceraian - Wadi, Hamzan (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2020)
Marriage is the merging of a bachelor and woman as husband and wife with the hope of forming a sakinah, mawaddah and warohmah family. According to other terms it can also mean Ijab Qobul which requires a relationship between a pair of people spoken by words intended to proceed to marriage, according to regulations required by Islam. Marriage is offered to people who really need it and they are able to pay for their marriages, dowry and to provide for physical and spiritual support. But if he really wants to get married while he has not been able to pay for it, then he should not get married first and to look after things that are not desirable, he should fast. Before the marriage of the prospective husband and wife should have known each other, this is to avoid something that will happen later after marriage, therefore by providing pre-marital counseling with an Islamic approach using the Qur'an is expected to prevent or overcome this problem until in the end the couple can find happiness and avoid divorce.